1998
DOI: 10.1073/pnas.95.26.15798
|View full text |Cite
|
Sign up to set email alerts
|

Desoxyepothilone B is curative against human tumor xenografts that are refractory to paclitaxel

Abstract: The epothilones are naturally occurring, cytotoxic macrolides that function through a paclitaxel (Taxol)-like mechanism. Although structurally dissimilar, both classes of molecules lead to the arrest of cell division and eventual cell death by stabilizing cellular microtubule assemblies. The epothilones differ in their ability to retain activity against multidrug-resistant ( Paclitaxel (Taxol**), Fig. 1, is currently used as the front-line therapeutic agent in a variety of solid forms of cancer including ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 21 publications
2
103
2
Order By: Relevance
“…However, like paclitaxel was effective in vincristine-resistant HL/ADR cells, another group of microtubule-active drugs can substitute for paclitaxel in paclitaxel-resistant HL/TX cells. In agreement with prior demonstrations that epothilones are effective against Pgp-expressing cells, 14 HL/TX cells were only marginally resistant to epothilones. Accordingly pretreatment with adriamycin, while protecting HL60 cells, did not protect either HL/ADR or HL/TX against epothilone A (data not shown) and epothilone B (Figure 6).…”
Section: Other Microtubule-active Drugs As the Second Agents In Paclisupporting
confidence: 91%
“…However, like paclitaxel was effective in vincristine-resistant HL/ADR cells, another group of microtubule-active drugs can substitute for paclitaxel in paclitaxel-resistant HL/TX cells. In agreement with prior demonstrations that epothilones are effective against Pgp-expressing cells, 14 HL/TX cells were only marginally resistant to epothilones. Accordingly pretreatment with adriamycin, while protecting HL60 cells, did not protect either HL/ADR or HL/TX against epothilone A (data not shown) and epothilone B (Figure 6).…”
Section: Other Microtubule-active Drugs As the Second Agents In Paclisupporting
confidence: 91%
“…Hence, studies are in progress to identify pure metabolites of microbial origin or any other components of the microbial cell that might have antitumor activity. One such example is the identification of secondary metabolites, epothilones A and B of the myxobacterium Sorangium cellulosum, which have shown both in vitro and in vivo cytotoxicity in various cancer cells, including MCF-7 cells (Chou et al, 1998;Altmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both MRP-and Pgp-expressing HL60 cells were still sensitive to flavopiridol (data herein), PS-341, and epothilone B. 15,22,24,25 In parental cells, caspase inhibitors B-D-fmk, Z-VAD-fmk, DEVD-fmk and Z-VEID-fmk abrogated drug-induced apoptosis. Caspase inhibitors prevented PARP cleavage, nuclear fragmentation, and sub-G1 peak on flow cytometry, and dramatically increased survival of normal cells.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that MRP1-expressing cells were not resistant to paclitaxel (PTX); and both MRP1 and PgP-expressing cells were not resistant to epothilone B (EpoB). 22,24,25 As shown in Figure 1a, Pgp-and MRP1-expressing HL-60 cells were normally sensitive to flavopiridol with the maximal cytotoxic effect at 300 nM. Since this dose of flavopiridol kills most of the cells by 36 h (Figure 1a), it was chosen for further experiments.…”
Section: Choosing Chemotherapeutic Agents and Caspase Inhibitorsmentioning
confidence: 99%